Chelovek s kinoapparatom . Man with a Movie Camera - Vertov, Dziga (VUFKU, 1929)
Vertov’s 1929 film records the progression of one full day synthesizing footage shot in Moscow, Riga, and Kiev. The film begins with titles that declare it “an experiment in the cinematic communication of visible events without the aid of intertitles, without the aid of a scenario, without the aid of theater.” It is often described as an urban documentary yet the subject of the film is also the film itself –from the role of the cameraman to that of the editor to its projection in a theatre and the response of the audience. It is a film within a film made with a range of inventive effects –dissolves, split screen, slow motion, freeze frame–all of which are now embedded in digital editing software.